THE EFFECT OF DAM BREED AND SOME NON GENETIC FACTORS ON THE GROWTH OF LAMBS BEFORE WEANING - Ahmad, Bashar Adham; Mahdi, MAAN F.; Ibrahim, Mostafa J.; Mahmood, Alaa Sh. (Diyala Agricultural Sciences Journal, 2015)
Used in this study, 27 ewes of different breeds (Awasi Turki, Awasi Local, Karadi, Hamdani) and the age range of 2-4 years to study the effect of breed the dam and age the dam and the month of birth and sex born and weight of the dam at birth in recipes growth of lambs of weight at birth and weight at weaning and increase the weight daily from birth until weaning and increase the weight daily gain . Through the comparison between the dam breed show a significant effect (p <0.05) breed in weight at birth, as it outperformed breed Alkaradi the rest of the breed is not observed any significant effect of breed in the rest of the qualities and found a significant effect (p <0.05) for the age of the dam in weight Birth where excelled ewes 4 years old on the rest of the ages. while for the month of January significant effect in weight at weaning and increase the weight and daily gain . through statistical analysis shows that the weight of the dam at birth significant effect (p <0.05) in weight at birth if dam weights outperformed the rest of the 60-66 kg weights, showing no significant effect of the sex of the born in the studied traits